ID-based on-line/off-line threshold signature scheme without bilinear pairing - Xiao-dong YANG; Chun-mei LI; Ting XU; Cai-fen WANG (Tongxin xuebao)
Based on the distributed key generation (DKG) protocol and verifiable secret sharing (VSS) protocol,an identity-based on-line/off-line threshold signature scheme was proposed in order to eliminate the cost of the certificate management in the public key cryptosystem and improve the performance of on-line/off-line threshold signature schemes.This scheme was proven to be robust and unforgeable under the discrete logarithm assumption.Analysis results show that the proposed scheme eliminates the problem of certificate management and pairing operation,and it greatly reduces computation cost of off-line threshold signature generation algorithm and signature verification algorithm.The new scheme is more efficient than the available on-line/off-line threshold signature schemes.